School administrator's complete letter book (Englewood Cliffs, N.J. : Prentice-Hall, 1984)
This is a valuable source book on school communication. It is a gold mine of tested, usable letters and others communiques, some of which can be used practically word-by-word from the book, while others can be adapted to your specific needs. It contains letters to be used and letters to be emulated.
Keywords: Correspondence; Schools; Records; School management and organization -- United States; Schools -- Records and correspondence; Letters